THE INFLUENCE OF DISCIPLINE AND ORGANIZATIONAL COMMITMENT ON THE PERFORMANCE OF EMPLOYEES OF PRESIDEN CIKARANG HIGH SCHOOL - Inna Nisawati Mardiani; Primaraga Sumantri Indra Wicaksana (Jurnal Ekonomi, 2023)
Human resources play an important role in determining the success of an organization in achieving its goals. SMA President is an educational institution that provides services in order to improve the quality of human resources. This role is closely related to producing generations with reliable quality human resources. This requires the organization to have good quality employee performance. This study aims to empirically examine the effect of discipline and organizational commitment on employee performance at President Cikarang Senior High School. The problems discussed in this study are: does discipline affect the performance of employees at SMA Presiden Cikarang; does organizational commitment affect employee performance at SMA President Cikarang; and how discipline and organizational commitment simultaneously affect the performance of employees at SMA Presiden Cikarang. The independent variables used in this research are discipline and organizational commitment. The dependent variable used in this study is employee performance. Samples were taken using saturated sampling techniques. Data collection was carried out by distributing questionnaires to respondents directly as many as 56 questionnaires. The statistical method used in this study is multiple regression analysis with t-test. The results of the study show that discipline and organizational commitment partially have a positive effect on employee performance. The F test proves that all independent variables have a positive and significant effect, and simultaneously have an effect on the dependent variable. The R2 test to determine the influence of all independent variables on the dependent variable in this study is 61.2%; while 32.8% is influenced by other factors. The results of this study prove that there is a positive influence on all hypothesized relationships. It is hoped that the findings from this study can be utilized in improving employee performance at President's High School or other similar organizations.